Modifikasi Perilaku Dinamik Struktur dengan Massa Terkonsentrasi - Hutahaean, Ramses Yohannes (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
One of the vibration problems that occurs at mining industries is when they increase production capacity as happen in the PT.Freeport Indonesia, and then we need to install a new machine with new rotary speed,Â so that it will increase the speed of rotary machine on the conveyor, if the speed of rotary machine close to the one of natural frequencies of the machine structure, this will cause resonance in the structure , so its is necessary to modify the dynamic behaviour of the structure to shift a certain number of these natural frequencies. In this study, shifting a certain number of natural frequencies of a dynamic system to desired values with the concentrated mass modifications is considered. The method to shifting a certain natural frequencies is based on the Sherman-Morrison formula and uses the receptances that are related to the modification coordinates of the original system. The method yields a set of nonlinear equations which equal the number of shifting frequencies, then the necessary masses are estimated by solving these equations numerically. The efficiency of the method is shown by various example. Its shown the method is very effective and can be used for real applications.